2018
DOI: 10.1177/0956462418758777
|View full text |Cite
|
Sign up to set email alerts
|

Vulval lichen planus–lichen sclerosus overlap

Abstract: Vulval lichen planus-lichen sclerosus overlap is an emerging observation. Few clinical reports exist with no reviews of literature. We present a focused update of this phenomenon and discuss a clinical case. We report a 63-year-old woman with a 20-year history of ulcerative vulvo-vaginitis, initially diagnosed as benign mucous membrane (cicatricial) pemphigoid. This led to prolonged treatment with oral corticosteroids with minimal improvement in symptoms. Subsequent complications of long-term use of systemic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…6 Cases of an overlap of VLP and VLS have been described, leading to the discussion of whether VLP and VLS are a continuum, rather than independent entities. 7,8 Patients with VLP should undergo gynecological assessment to exclude vaginal involvement. The major aims of treatment are symptomatic relief and the prevention and/or limitation of scarring.…”
Section: Introductionmentioning
confidence: 99%
“…6 Cases of an overlap of VLP and VLS have been described, leading to the discussion of whether VLP and VLS are a continuum, rather than independent entities. 7,8 Patients with VLP should undergo gynecological assessment to exclude vaginal involvement. The major aims of treatment are symptomatic relief and the prevention and/or limitation of scarring.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study shows that patients with LS have an increased risk for thyrotoxicosis, which is in line with previous studies [ 27 ]. Lichen ruber planus is commonly found coexisting with LS lesions [ 18 ]. The strong association presented in this study supports this.…”
Section: Discussionmentioning
confidence: 99%
“…The association between LS and thyroid disease has been established in women, but is not clear in men [ 2 ]. Several case reports and smaller studies have found an association between psoriasis [ 16 ], vitiligo [ 17 ], lichen planus [ 18 ], alopecia areata and ulcerative colitis [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the diagnosis was clinical; histology was reserved to the cases refractory to first line treatments and/or when suspicious lesions were observed. Nevertheless, while some authors defend that clinical appearance are nonspecific for vulvar LP and often shared with other dermatosis, like LS, 14,22 among different guidelines the use of histology for the diagnosis of vulvar dermatosis is not consensual. [23][24][25] In the light of these conflicting positions about the diagnostic criteria of vulvar LP and considering that we normally used the clinical criteria for establishing the diagnosis, it could be seen as a limitation of this study.…”
Section: Strengths and Limitationsmentioning
confidence: 99%